2003
DOI: 10.1038/sj.thj.6200338
|View full text |Cite
|
Sign up to set email alerts
|

HPA-genotyping and antiplatelet antibodies in female blood donors

Abstract: Cases of passive alloimmune thrombocytopenia have been reported due to transfusions of blood products with antiplatelet antibodies. The aim of our study was to search for antiplatelet antibodies in HPA-homozygous blood donor women once pregnant and also to perform, in case of positivity, a retrospective analysis of platelet counts of the recipients of their blood products. HPA-1, -2, -3 and -5 genotyping were performed on 500 platelet donors (42% women). Circulating antiplatelet antibodies were screened for by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
3
13
2
Order By: Relevance
“…HPA‐3 frequencies described previously for São Paulo blood donors (Conti et al , ), Brazilian African descendants (Castro et al , ) and Slovenian and Swiss descendents (Boehlen et al , ) did not differ from results found in the Amazonas blood donors. This system was one of the most polymorphic systems found in this population, after HPA‐15, with 24·99% of mismatch probability.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…HPA‐3 frequencies described previously for São Paulo blood donors (Conti et al , ), Brazilian African descendants (Castro et al , ) and Slovenian and Swiss descendents (Boehlen et al , ) did not differ from results found in the Amazonas blood donors. This system was one of the most polymorphic systems found in this population, after HPA‐15, with 24·99% of mismatch probability.…”
Section: Discussionmentioning
confidence: 41%
“…The genotype and allele frequencies were estimated by direct counting, and the results were compared with the values published for blood donors and/or healthy individuals worldwide (http://www.ebi.ac.uk/ipd/hpa/freqs_1.html). A 2 test or Fisher's exact test was performed to individually compare the allele frequencies of each HPA polymorphic system between the Amazonas blood donors and the data reported for 38 population groups worldwide (Muniz-Diaz et al, 1993;Santoso et al, 1993;Holensteiner et al, 1995;Kekomaki et al, 1995;Kim et al, 1995;Tanaka et al, 1995;Steffensen et al, 1996;Carlsson et al, 1997;Merieux et al, 1997;Drzewek et al, 1998;Seo et al, 1998;Castro et al, 1999;Korinkova et al, 1999;Mojaat et al, 1999;Rozman et al, 1999;Sellers et al, 1999;Mazzucco et al, 2000;Nogues et al, 2000;Bennett et al, 2002;Ferrer et al, 2002;Boehlen et al, 2003;Jones et al, 2003;Randen et al, 2003;Shih et al, 2003;Halle et al, 2004Halle et al, , 2005Kulkarni et al, 2005;Feng et al, 2006;Pavkovic et al, 2006;De La Vega Elena et al, 2008;Bhatti et al, 2010;Pavic et al, 2010;Tan et al, 2012;Conti et al, 2014). A hierarchical classification of all analysed populations was carried out based on a allele frequencies from five HPA polymorphic systems using Cluster 3·0 and Java Tree View software packages (Eisen Lab, University of California, Berkeley).…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study found that up to 4.2 percent of previously pregnant female blood donors had circulating PLT alloantibodies 27 . Another study showed that as many as 2.5 percent (3/122) of HPA‐homozygous female PLT donors who were previously pregnant carried the PLT‐specific antibodies 28 . Fortunately, none of the 55 blood components from these women resulted in thrombocytopenia due to passive transfer of PLT antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HPA-5 antibodies are known to be less immunopathegenic than anti-HPA-1a antibodies; indeed most cases of passive thrombocytopenia reported in the literature are secondary to the transfusion of blood products containing anti-HPA-1a antibodies. 15,16 However, a case of transient and moderately severe thrombocytopenia caused by passive transfusion of plasma containing anti-HPA-5b antibodies has also been reported. 17 It thus appears that most cases of NAIT among Caucasians are caused by anti-HPA-1a, which contrastingly is much reduced in our African population.…”
Section: Discussionmentioning
confidence: 99%